Metode mjerenja i prognoziranja prometa na autobusnim kolodvorima - Štefančić, Gordana; Božičević, Damir (Promet - Traffic&Transportation, 2012)
In order to have fluctuations in traffic reduced to the minimum and on to a predictable scale, the paper deals with the measuring and forecasting of passenger flows at bus stations. Particular attention has been fixed on traffic forecasting by the method of correlative analysis. The examination of respective indices, coefficient of correlation, and value trend have all comifired the adequacy of the Gompertz trend, being of particular importance for the projections of fixture demand for traffic services.